2006
DOI: 10.1007/s00359-006-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in avian auditory evoked responses to tones: a comparative analysis of Carolina chickadees, tufted titmice, and white-breasted nuthatches

Abstract: We tested for seasonal plasticity of the peripheral auditory system of three North American members of the Sylvioidea: Carolina chickadees (Poecile carolinensis), tufted titmice (Baeolophus bicolor), and white-breasted nuthatches (Sitta carolinensis). We measured three classes of auditory evoked responses (AER) to tone stimuli: sustained receptor/neural responses to pure-tone condensation waveforms, the frequency-following response (FFR), and the earliest peak of the AER to stimulus onset (tone onset response)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 55 publications
3
52
0
Order By: Relevance
“…Note, however, that it is unclear whether thresholds under more realistic, noisy conditions vary seasonally, because absolute thresholds do not necessarily predict thresholds in noise (Langemann et al, 1998;Lohr et al, 2003). Previous studies of seasonal auditory plasticity found no variation in thresholds of the plainfin midshipman and northern leopard frog (Sisneros et al, 2004;Goense and Feng, 2005) or in ABR latency of Carolina chickadees, house sparrows and tufted titmice (Lucas et al, 2002;Lucas et al, 2007). White-breasted nuthatches, however, had shorter ABR latency in winter than in spring, suggesting possible seasonal variation in auditory thresholds.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Note, however, that it is unclear whether thresholds under more realistic, noisy conditions vary seasonally, because absolute thresholds do not necessarily predict thresholds in noise (Langemann et al, 1998;Lohr et al, 2003). Previous studies of seasonal auditory plasticity found no variation in thresholds of the plainfin midshipman and northern leopard frog (Sisneros et al, 2004;Goense and Feng, 2005) or in ABR latency of Carolina chickadees, house sparrows and tufted titmice (Lucas et al, 2002;Lucas et al, 2007). White-breasted nuthatches, however, had shorter ABR latency in winter than in spring, suggesting possible seasonal variation in auditory thresholds.…”
Section: Discussionmentioning
confidence: 97%
“…Single-unit studies of the auditory nerve in plainfin midshipman fish [Porichthys notatus (Sisneros et al, 2004)] and auditory midbrain in northern leopard frogs [Rana pipiens (Goense and Feng, 2005)] showed seasonal variation in the temporal precision of neural responses to the acoustic structure of artificial calls. In songbirds, Lucas and colleagues found preliminary evidence of seasonal variation in auditory brainstem responses (ABRs) of four species, including the house sparrow (Passer domesticus) studied here (Lucas et al, 2002;Lucas et al, 2007). ABRs are voltage waveforms recorded from the scalp that reflect the summed neural onset response of the auditory nerve and brainstem nuclei to sound (Hall, 2007).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mammals show marked decline in auditory sensitivity with age, particularly at higher frequencies within their respective audible ranges (for a review, see Ohlemiller, 2006). Songbirds have been shown to have remarkably stable baseline auditory thresholds throughout ontogeny (Langemann et al, 1999) with species-specific seasonal changes (Lucas et al, 2002;Lucas et al, 2007), whereas studies in fishes have yielded conflicting results (Higgs et al, 2003;Higgs et al, 2002;Iwashita et al, 1999;Kenyon, 1996;Popper, 1971;Sisneros and Bass, 2005). We have investigated peripheral auditory plasticity in a teleost fish, the plainfin midshipman (Porichthys notatus Girard 1854; family Batrachoididae), that shows seasonal, reproductive state-dependent plasticity in the ability to encode the upper harmonics of vocalizations (Fig.1A,B).…”
Section: Introductionmentioning
confidence: 99%
“…In seasonally breeding songbirds, there are pronounced hormone-driven seasonal changes in volume and neural morphology of song nuclei, which are accompanied by changes in stereotypy, duration, and production rate of song (Nottebohm, 1981;Ball et al, 2004;Brenowitz, 2004). Only recently have seasonal changes in avian neuronal activity begun to be studied, with research generally focusing on how auditory stimuli are differentially processed (Del Negro and Edeline, 2002;Lucas et al, 2002Lucas et al, , 2007Del Negro et al, 2005) or on how changes in the electrophysiological properties of song nuclei might underlie changes in song behavior (Park et al, 2005;Meitzen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%